An Eco-friendly Iron Cathode Electro-Fenton System Coupled With a pH-Regulation Electrolysis Cell for p-nitrophenol Degradation - Jiang, Bo (Frontiers in Chemistry, 2022)
The high consumption of salt reagents and strict pH control are still the bottlenecks for the full-scale application of Fenton reaction. In this work, a novel eco-friendly iron cathode electrochemical Fenton (ICEF) system coupled with pH-regulation divided electrolysis cell was developed. In pH-regulation divided electrolysis system, the desired pH for an effective Fenton reaction and for a neutral treated media could be obtained by H2O splitting into H+ and OH− at the anode and cathode, respectively. In ICEF system, iron plate was used as the cathode to inhibit the release of iron ions and promote the reduction of Fe3+ to Fe2+. It was found that when a potential of 1.2 V/SCE was applied on the iron cathode, 98% p-nitrophenol was removed in the combined system after 30 min with continuously adding 200 mg/L H2O2. Meanwhile, COD and TOC removal efficiency of 79% and 60% was obtained, respectively. In this case, the conductivity just slightly increased from 4.35 to 4.37 mS/cm, minimizing the increase of water salinity, as compared with the conventional Fenton process. Generally, this combined system was eco-friendly, energy-efficient and has the potential of being a promising technology for the removal of biorefractory organic pollutants from wastewaters.